ANALISIS PERTUMBUHAN EKONOMI PROVINSI BALI DI MASA PANDEMI COVID-19 PADA SEKTOR PARIWISATA - Aprilianti, Indah; Utama, Made Suyana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 2 (2024): Vol.13.No.2. FEBRUARI 2024 [91-160]DO - 10.24843/EEP.2024.v13.i02.p02, 2024)
The success of the development of a region can be measured through indicators of economic growth which have increased showing that regional development is evenly distributed so that it touches all levels of society. This study aims to analyze the effect of the number of hotel rooms, employment, and the number of tourist visits on the economic growth of the Bali Province in the tourism sector. This study uses panel data, which is a combination of time series data and cross sections (9 regencies/cities in Bali Province) with a total of 45 observations. The data source used in this research is a secondary data source. The analysis technique used in this research is panel data analysis technique. The results of this study indicate that the simultaneous and partial influence of the number of hotel rooms, employment, and the number of tourist visits has had on the economic growth of the Province of Bali during the Covid-19 pandemic in the tourism sector. Partially, the number of hotel rooms has an effect, employment has an effect and the number of tourist visits has no effect on the economic growth of the Province of Bali during the Covid-19 pandemic in the tourism sector. keyword : Number Of Hotel Rooms, Employment, Number Of Tourist Visit. Klasifikasi JEL: L85, E24, L83